Analisis Adopsi AI pada Desain UI/UX di Provinsi Bali - Ashram Pratama, I Gede Octa Werdhi (Universitas Multi Data Palembang, 2025)
This study aims to analyze the level of adoption and perceptions of UI/UX designers regarding artificial intelligence (AI) technology in design practices in Bali, as well as to explore designers’ perspectives and the challenges of its implementation. Bali was chosen as the research location because it is a center of growth for the digital creative industry, which increasingly requires technological support to enhance competitiveness. The study employed a mixed-methods approach with an exploratory-descriptive nature. Quantitative data were collected through a questionnaire based on the Technology Acceptance Model (TAM) completed by 31 professional UI/UX respondents, while qualitative data were obtained from semi-structured interviews with seven participants. Quantitative analysis was carried out using descriptive statistics, and qualitative data were analyzed using a thematic approach. The findings indicate that AI adoption is at a high level. AI is perceived as beneficial, relatively easy to use, and considered a supportive tool that accelerates ideation, planning, and UX writing, yet it cannot replace human creativity and empathy. Key challenges include outputs that do not meet expectations, limited literacy, costs, ethical concerns, and infrastructure constraints. This study highlights the importance of adopting AI strategically and ethically in Bali’s creative industry while contributing to the literature on technology adoption in digital design.